MIKHAIL’S PERSONAL IDENTITY CONSTRUCTION IN PAULO COELHO’S THE ZAHIR (Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
Language is used not only for communication but also to reflect personality as well as to construct identity. The aim of this study is to examine Mikhail’s personal identity construction through his language use. Therefore, the labels attached to him and his stancetakings are investigated. In conducting the study, the writer applies Discourse Analysis. Descriptive research is used in order to identify, classify, and describe his utterances which contain the use of label and stancetaking. The findings reveal that he is a kind of arrogant person based on the values of the labels given by self. Furthermore, the more he puts label on himself in a society, the less he gets label from others. The findings also indicate that his tendencies to position himself along epistemic scale ‘certainty’ and disalign with his interlocutors in talk-in-interaction have successfully transformed him into a superior person.